The Vision of Hungarian Folk Dance in Diaspora: Folk Dance Teaching Methodology Work Plan for the Uruguayan Tündérkert Folk Dance Ensemble - Patricia Alejandra Brum Kagyerják (Tánc és Nevelés, 2023)
How can Hungarian folk dance education be implemented in the Hungarian diaspora communities in South America, particularly in Uruguay, with goal-oriented and development-focused results? Following linguistic assimilation, Hungarian folk dance is one of the most important pillars keeping the Hungarian community in Uruguay alive. In order for Hungarian identity to continue to remain thrive in Uruguay, conscious development in the field of dance education is essential. The work plan presented in this study aims to help dance teachers efficiently and accurately organize, plan, and deliver dance classes, thus achieving improved results in regard to dance technique and general knowledge of Hungarian folklore.